2021
DOI: 10.1186/s43058-021-00245-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Causal Pathways and Targets of Implementation Variability for EBP use (Project ACTIVE): a study protocol

Abstract: Background Advancing causal implementation theory is critical for designing tailored implementation strategies that target specific mechanisms associated with evidence-based practice (EBP) use. This study will test the generalizability of a conceptual model that integrates organizational constructs and behavioral theory to predict clinician use of cognitive-behavioral therapy (CBT) techniques in community mental health centers. CBT is a leading psychosocial EBP for psychiatric disorders that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…A recent theory of change highlights the importance of integrating both psychological and organizational theories of behavior change into implementation research when evaluating causal pathways (see Fig. 1 ) [ 26 ]. Psychological theories of behavior change can provide insight into why EI practitioners do or do not use the components of caregiver coaching and inform strategies to improve its implementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent theory of change highlights the importance of integrating both psychological and organizational theories of behavior change into implementation research when evaluating causal pathways (see Fig. 1 ) [ 26 ]. Psychological theories of behavior change can provide insight into why EI practitioners do or do not use the components of caregiver coaching and inform strategies to improve its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Leading behavior change theories posit that an individuals’ intention to perform a certain behavior is the most proximal determinant of that behavior when individuals have the ability to act on their intentions [ 27 ]. Intentions represent an individual’s motivation to perform a certain behavior and are malleable targets for implementation research [ 26 ]. The determinants of intention are attitudes (e.g., whether the practitioner “likes” or “dislikes” coaching caregivers), descriptive norms (e.g., whether the practitioner perceives that other practitioners like them use coaching), injunctive norms (e.g., whether the practitioner perceives that important others, such as supervisors, expect them to use it), and self-efficacy (e.g., whether the practitioner believes that they have the necessary skills to provide effective coaching).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the results from psychology, the implementation science literature has started to document how practitioners’ attitudes can vary greatly among evidence-based practices [ 9 12 ]. For example, we have found that therapists’ attitudes vary towards different components of cognitive-behavioral therapy [ 10 ].…”
mentioning
confidence: 99%
“…For example, we have found that therapists’ attitudes vary towards different components of cognitive-behavioral therapy [ 10 ]. Given this variability, a measure of attitudes towards “evidence-based practice” or even “cognitive behavioral therapy” would sacrifice psychometric performance, including predictive validity [ 9 12 ]. Depending on the specific evidence-based practice, other psychological variables also can vary [ 9 12 ].…”
mentioning
confidence: 99%